(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Asociación de Cerveceros Caseros del Perú (ACECAS) is a non-profit civil organization that was formed in 2017. During its existence, it has constantly dedicated itself to promoting the production of craft beer and the dissemination of the "beer culture" in Peru and mainly in the city of Lima. To achieve its objective, ACECAS, has been in charge of associating at least 100 homebrewers who before its existence were dedicated to the production of the product in an amateur way and only following the steps that they themselves could find out from their own experience. ACECAS has managed to train new homebrewers with a projection to develop in the world of artisan production for their own benefit or for an eventual commercialization of their products; In addition, the association has been in charge of promoting workshops, courses, visits to plants, joint cooking, and other types of collaborations to bring together the associates and thus promoting networking between them. During the pandemic, the association managed to continue with its activities taking advantage of virtuality, thus being able to reach more people not only from Lima, but from other parts of Peru who also consider themselves lovers of craft beer. The purpose of this article is to explore the results of the study carried out in order to verify whether ACECAS actions effectively have an impact on the associativity of its members and on the leadership that the same organization exercises over them.